Devising technology for extinguishing oil tanks using compressed foam by sub-layer technique - Kovalyshyn, Vasyl; Velykyi, Nazarii; Kovalyshyn, Volodymyr; Voitovych, Tetiana; Bun, Rostyslav; Novitskyi, Yaroslav; Firman, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2024)
Tank facilities storing various combustible substances are a potential source of danger for the environment and human life. Fires in tanks can occur for various reasons: technical malfunctions, human factors, military operations, natural phenomena. One of the effective methods for extinguishing such fires is "sublayer" extinguishing with the help of foam of low multiplicity. The possibility of "sub-layer" extinguishing with the help of compression foam, which has unique properties, has been considered. The object of this study is the processes of stopping combustion during fire extinguishing in steel tanks for the storage of petroleum products with the use of foaming agents of increased stability, which ensure the generation of compression foam in a "sub-layer" way. A mathematical model of the movement of a submerged non-free jet of foam in the medium of motor fuel is given, which adequately describes the real physical processes that occur during "sublayer" quenching of vertical steel tanks. According to the research, it was established that the use of foam with a multiplicity of 10 (K10) is 1.56 times more effective in serving time than the use of foam with a multiplicity of 5 (K5). From an economic point of view, K10 foam also has greater advantages as the costs of the foaming agent during its generation are 3.1 times lower than when using K5 foam. The simulations demonstrated that the foaming agent consumption of the K10 foam is lower than the foaming agent consumption of the K5 foam and results in a different amount of foam coming to the surface. The simulations also showed that the volume of K5 foam increases proportionally with the feeding time, while the volume of K10 foam increases disproportionally and starts to decrease after half the time. The results from the implementation of the mathematical model were fully consistent with the results from experimental studies on extinguishing a model fire of class B